Identification of Culicidae Family Diversity as Vector Control Management and Mosquito-Borne Disease Prevention in Universitas Gadjah Mada, Yogyakarta - Dila Hening Windyaraini; Fiola Tiarani Siregar; Asti Vanani; Titi Marsifah; Soenarwan Hery Poerwanto (Universitas Airlangga, 2020)
Introduction: Family Culicidae was the presence of a mosquito that had a potential vector to cause the spread of dengue fever and some diseases. Mosquito diversity could be different due to human and environmental factors in those regions. This study aims to identify mosquito (family Culicidae) diversity and characteristics of breeding places as vector control management and mosquito-borne disease prevention in the area of Universitas Gadjah Mada, Yogyakarta. Method: The study was conducted from April to September 2018. A sampling of mosquito larvae and observation of mosquitoes breeding places characteristics were carried out inside and outside the Universitas Gadjah Mada campus building which was divided into 5 clusters, there were Science and Engineering cluster, Medica, Agro, Vocational School, and Social Science. Mosquito diversity in the Universitas Gadjah Mada campus area was analyzed used the Shannon-Wienner diversity index. Result and Discussion: Mosquitoes found in the area of Universitas Gadjah Mada consist of two phases with total number 153 larvae and pupae, namely Aedes aegypti, Aedes albopictus, Anopheles spp., and Culex spp. The mosquito with the highest number of larvae and pupae was Aedes albopictus, while Anopheles spp. Only found 1 pupa phase. The number of obtained containers was 50 containers, with 6 positive containers of mosquito larvae. Mostly, the type of container found with mosquito larvae was bucket. For each container observed, the temperature and pH of water in the container were measured and it was found that the water temperature reached 24 – 28°C with pH 6 – 7. Conclusion: Mosquito diversity from all of the areas in Universitas Gadjah Mada was grouped as a medium category, with the greatest number of mosquito larvae were found in Science and Engineering cluster. Containers were located in the open area had more mosquito larvae. Mosquito control is focused on environmental management, biological control, and chemical use.